Gonadal lesions of female sea urchin (Psammechinus miliaris) after exposure to the polycyclic aromatic hydrocarbon phenanthrene (Marine Environmental Research, 2010)
Abstract Histopathological alterations in the reproductive tissue of the female sea urchin Psammechinus miliaris after exposure to the polycyclic aromatic hydrocarbon (PAH) phenanthrene were investigated using light microscopy. Sexually mature sea urchins were exposed to 500 ?g L-1 phenanthrene for 20 days. A severe disorganisation of the acinal structure of the gonads was observed in phenanthrene-treated animals, mainly as a result of aggregates of degenerating previtellogenic oocytes. Growth and maturation of previtellogenic oocytes were inhibited, whereas there were no obvious effects on vitellogenic oocytes and mature ova. The acinal wall showed signs of fibrosis as well as dilation of the two epithelial layers. Phenanthrene severely affected the reproductive function of the sea urchins since a proper oogenesis of the ovarian tissue is very unlikely. Generally, the observed alterations are similar to histopathological changes in reproductive tissue in other invertebrates after exposure to PAHs and oil. correspondance: Corresponding author. (Kohler, A.) Angela.Koehler@awi.de (Kohler, A.) Alfred Wegener Institute for Polar and Marine Research in the Helmholtz Association--> , Am Handelshafen 12--> , 27570 Bremerhaven--> - GERMANY (Schafer, S.) Alfred Wegener Institute for Polar and Marine Research in the Helmholtz Association--> , Am Handelshafen 12--> , 27570 Bremerhaven--> - GERMANY (Kohler, A.) GERMANY Received: 2008-11-12 Revised: 2009-04-29 Accepted: 2009-05-07